2011
DOI: 10.1007/s10267-010-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

A survey of proteases in edible mushrooms with synthetic peptides as substrates

Abstract: The protease activities in six edible mushrooms were surveyed using synthetic fluorogenic substrates that have different specificities for each protease group. The activity was determined by measuring the fluorogenic intensity of the 7-amino-4-methylcoumarin (AMC) liberated by an enzyme. Various types of activities were found in all mushrooms, and their activities depended largely on the mushroom species, but also on the pH and localization. Flammulina velutipes and Pleurotus eryngii had the widest and highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Therefore, the incorporation of mushroom powder not only dilutes the gluten and alters the water behavior of the final dough, but also a source of reducing agents and, as a result, this weakens the protein matrix. Furthermore, some researchers have reported the existence, and function, of mushroom proteases (Nakamura, Iketani, & Shioi, 2011;Nishiwaki, Asano, & Ohyama, 2009;Wang & Ng, 2001), which could damage the gluten network during the bread making and make negative effects on the dough quality. The proteins and dietary fiber resulting from the mushroom powder incorporation may have a negative effect on the well-formed protein-starch complex within the bread matrix (Sun et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the incorporation of mushroom powder not only dilutes the gluten and alters the water behavior of the final dough, but also a source of reducing agents and, as a result, this weakens the protein matrix. Furthermore, some researchers have reported the existence, and function, of mushroom proteases (Nakamura, Iketani, & Shioi, 2011;Nishiwaki, Asano, & Ohyama, 2009;Wang & Ng, 2001), which could damage the gluten network during the bread making and make negative effects on the dough quality. The proteins and dietary fiber resulting from the mushroom powder incorporation may have a negative effect on the well-formed protein-starch complex within the bread matrix (Sun et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…So the difference between such ratios of wheat flour and mushroom powder may play a role in the decreased extensibility. Furthermore, some researchers have reported the existence, and function, of mushroom proteases (Nakamura, Iketani, & Shioi, 2011;Nishiwaki, Asano, & Ohyama, 2009;Wang & Ng, 2001), which could damage the gluten network during the bread making and make negative effects on the dough quality.…”
Section: Resultsmentioning
confidence: 99%
“…No mercado mundial de enzimas as proteases predominam na indústria de detergentes, farmacêutica, cerveja, couro, alimentos, como coagulante na fabricação de queijo e para recuperação da prata usada no filme de raios-X (GENÇKAL, 2004;CUI et al, 2007;SABOTIC et al, 2007;DABOOR et al, 2010). Proteases também participam da síntese e degradação de proteínas, da conidiogênese e descarga conidial, germinação, modificação enzimática, nutrição e regulação da expressão gênica (CUI et al, 2007;NAKAMURA et al, 2011;ZHENG et al, 2011).…”
Section: Introductionunclassified
“…Flammulina velutipes, P. ostreatus, Grifola frondosa, Tricholoma saponaceum, Armillaria mellea e Cordyceps militaris estão relatadas nas citações de Park et al (2007) e Nakamura et al (2011).…”
unclassified
“…In recent years, many researches had shown that edible mushrooms are sources of many enzymes, including proteases (Mokochinsk et al, 2015). The proteases participate in various physiological functions and they are very important technological tools in several areas such as food, detergent and pharmaceutical industries (Nakamura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%